2019
DOI: 10.3390/medicina55050212
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Depressive Disorders in Pregnant Women—A Systematic Review

Abstract: Background and Objectives: Pregnancy is a unique period in the life of every woman. The lifestyle of a pregnant woman has a significant impact on her and her child’s health. Regular physical activity is one of the elements that help maintain normal mental and physical well-being. In pregnant women who regularly have moderate physical activity, there is a lower risk of developing obesity and overweight. Physical exercises have an impact on maintaining proper muscular tonus, reduce pain and prepare for the exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 48 publications
4
40
1
2
Order By: Relevance
“…Most commonly, those women who engaged in only light physical activity during pregnancy were significantly less likely to have psychological distress during pregnancy, whereas those women who engaged in a combination of all light, moderate and vigorous physical activity during pregnancy were more likely to have psychological distress during pregnancy and depression after childbirth. Most studies have concluded that regular physical exercise during pregnancy has a beneficial impact on psychological health 40 , but our results are somewhat similar to those of other studies using general population data 41,42 . The present study is one of the few studies to show that different combinations of varying intensities of physical activity had different patterns of associations with psychological outcomes among pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…Most commonly, those women who engaged in only light physical activity during pregnancy were significantly less likely to have psychological distress during pregnancy, whereas those women who engaged in a combination of all light, moderate and vigorous physical activity during pregnancy were more likely to have psychological distress during pregnancy and depression after childbirth. Most studies have concluded that regular physical exercise during pregnancy has a beneficial impact on psychological health 40 , but our results are somewhat similar to those of other studies using general population data 41,42 . The present study is one of the few studies to show that different combinations of varying intensities of physical activity had different patterns of associations with psychological outcomes among pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…However, exercising during pregnancy helps maintain a stable psychological state. Exercise not only alleviates the stress, anxiety, and depression symptoms that occur during pregnancy [2], but also reduces the duration and pain of labor and facilitates postpartum recovery [7]. A meta-analysis of the impact of physical activity on pregnant women reported that moderate-intensity activities lower excessive pregnancy weight gain, pregnancy diabetes, and postpartum depression [11].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of physical activity during pregnancy include improved physical fitness and reduced risks of excessive weight gain, pre-eclampsia, and pre-term birth. During pregnancy, women experience involuntary physical and mental changes, and the maternal physiological system is transformed to embrace fetal growth and development [1,2]. According to a recent statistical report, the neonatal mortality rate in Korea is below the Organization for Economic Cooperation and Development (OECD) average at 2.8 per 100 births; the stillbirth rate, however, is higher than the OECD average, at 7.8 per 100 births [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activities also eliminate the risk of developing depression during pregnancy and are a safe form of preventative treatment. Women who were also active before or during pregnancy had a lower risk of developing depressive disorders compared to physically inactive women (for a review see Kołomańska et al [66]). According to the ACOG (American College of Obstetricians and Gynecologists) recommendation, physical activity should be resumed after childbirth as soon as possible and whenever it is safe [39].…”
Section: Discussionmentioning
confidence: 99%